Emotion specific neural activation for the production and perception of facial expressions. (June 2020) - Krautheim, Johannes T.; Steines, Miriam; Dannlowski, Udo; Neziroğlu, Gizem; Acosta, Henriette; Sommer, Jens; Straube, Benjamin; Kircher, Tilo
Abstract: The distinction between different facial emotions is crucial for interpersonal communication. Shared neural circuits for facial emotion production and perception are considered to facilitate the ability to understand other's emotional state via mirror neuron mechanisms. Little is known about how diverse emotions differentially activate the Mirror Neuron System (MNS) during facial expression processing. In a functional magnetic resonance imaging (fMRI) task, 178 healthy subjects perceived and produced emotional (happy vs angry) and non-emotional (lip-protrusion vs no movement) facial expressions. Dynamic facial expressions were displayed as 5 sec video clips. We identified three overlapping networks of neural activation for happy, angry, and non-emotional (lip-protrusion) facial expression production and perception. Importantly, this overlap was largely due to the common motor component of facial expressions. However, for happy facial expressions, we found specific MNS activation in the right temporal pole. For angry facial expressions we found such activation in the left inferior frontal gyrus, pars orbitalis, and the cerebellum (lobules VII and VIII). We extend knowledge on mirror neuron mechanisms as our results provide evidence for emotion specific shared neural activation for the production and perception of facial emotions. This emotion specific representation of other's emotion in one's own neural production system might facilitate understanding of other's mental or emotional states.